Adoption of Biogas Technology to Ordinary Pit Latrines in Uganda. - Kibet, Benson (Kabale University, 2023)
The highest population of Ugandans live in rural areas. This segment of population is mainly dependent on use of biomass consisting of firewood, charcoal, straw, crop residues to meet its energy demand for cooking and other domestic needs. The aim of this project is to provide detailed analysis of how to generate biogas energy from ordinary pit latrine. To achieve this, the existing pit latrines were first studied, and then different biogas technologies were also studied. An appropriate technology was then selected and the design equations covering the volume of the digester, inlet and outlet chambers were developed considering the shape of the digester. The final layout of biogas pit latrine was developed. This study was motivated due to inefficient exploitation of biogas from ordinary pit latrines. The developed layout ofbiogas pit latrine has been found to be appropriate for biogas production using human waste as substrate. Proper sealing of the gas storage facility is emphasized to avoid leakage and occasional maintenance is highly encouraged.